Analysis of droplet dynamic behavior and condensation heat transfer characteristics on rectangular microgrooved surface with CuO nanostructures. (March 2019) - Peng, Qi; Jia, Li; Dang, Chao; An, Zhoujian; Zhang, Yongxin; Yin, Liaofei
Highlights: The two-tier structured surface was fabricated by machining and chemical oxidation. The suspension, suction and strong self-oscillation of droplets were observed. The microgrooved surface with CuO nanostructures increased heat flux by 55–102%. Abstract: Condensation is a ubiquitous phase-change phenomenon in nature and has been widely adopted in various energy-intensive industrial application. Many efforts have been focused on regulating droplet dynamics to enhance the condensation heat transfer by developing micro/nanostructured surface. In this work, a microgrooved surface with CuO nanostructures was fabricated by combination of simple machining and scalable self-limiting chemical oxidation method for regulating droplet dynamic behavior. The wettability, droplet dynamics and heat transfer characteristics on such surface were compared with that on plain and microgrooved hydrophobic surfaces. The anisotropic wettability was observed on microgrooved surface and enhanced by creating nanostructures. 15–43% higher heat flux was reached on microgrooved hydrophobic surface compared to plain hydrophobic surface due to an increase of effective heat transfer area, the sweeping effect of liquid columns for droplets on adjacent plateaus and cooperation of liquid columns flowing and liquid bridges sliding. Several novel droplet dynamic behaviors that the suspension of large droplets, suction of spindle-shaped droplets and strong self-oscillation of falling droplets were observed on the microgrooved surface with nanostructures and enhanced the condensation heat transfer. Compared with plain hydrophobic surface, the heat flux was enhanced up to 55–102%.